The Return of Displaced Nuer in Southern Sudan: Women Becoming Men?. Issue 5 (12th September 2013) - Grabska, Katarzyna
ABSTRACT: Conceptualizing war‐time displacement as a catalyst for social change, this article examines the gendered emplacement experiences of returnee displaced women in the aftermath of the recent (1983–2005) civil war in South Sudan. The article attempts to shed light on the strategies of returnee women in transforming and contributing to their communities in the context of an independent South Sudan. It focuses specifically on their gendered emplacement strategies to access land, livelihoods and political rights. Through these diverse actions, some women contest and reconfigure gender identities while others reinforce unequal power relations within their households and communities. These gendered emplacements emphasize the hybridity of place, identity and self in processes of social transformation.